Fire Hazard in Chattogram City Corporation Area: A Critical Analysis of Its Causes and Mitigation Measures - Hasan, Muhammad Rashidul; Kauser, Md. Rakibul Hasan; Ibrahim, Jihan (Frontiers in Sustainable Cities, 2021)
Fire can have its origin either in natural or human activities resulting in death and/or property damage in a very short period of time. To develop fire hazard-resilient cities proper attention should be given to all possible sections of development to facilitate the service. Chattogram City is the second largest city of Bangladesh. Due to rapid rate of urbanization and unplanned growth of urban centers; hazards like fire have become a menace for the Chattogram City Corporation (CCC) area. So, the main objective of this research is to identify the nature of the fire hazard by analyzing frequency and intensity over time through different checklists and analyzing the existing firefighting capacity. In addition to past fire incident records, a direct questionnaire survey was utilized and expert opinion was solicited for primary data collection. Using geographical information systems (GIS) techniques, this study found that nine fire stations in the CCC area exhibited different frequency and intensity in different categories such as type of structure, land use, source of fire, damage, and losses in last 5 years. The number of fire incidents increased from 200 to 675 which indicates that the frequency increased over time. Among 2,514 fire accidents, 47% occurred in residential areas and 27% occurred in commercial areas. Fire intensity also varied with seasonal variation over a year. Within the last 5 years, the Chattogram City Corporation dealt with a 179,091,200 BDT financial loss and 83 people were injured, of which 15 were due to fire accidents. One the other hand, only nine fire stations serve the 155 sq.km area and 6 million people live in the CCC area which is 17 and 19 times larger than that of Bangkok and Oklahoma City. Finally, this data-driven approach and findings could help emergency planners to take necessary steps for improving firefighting capability to ensure better fire safety and resiliency.